The ubiquitination code: a signalling problem - Woelk, Tanja; Sigismund, Sara; Penengo, Lorenza; Polo, Simona (Cell division, 2007)
Ubiquitin is a highly versatile post-translational modification that controls virtually all types of cellular events. Over the past ten years we have learned that diverse forms of ubiquitin modifications and of ubiquitin binding modules co-exist in the cell, giving rise to complex networks of protein:protein interactions. A central problem that continues to puzzle ubiquitinologists is how cells translate this myriad of stimuli into highly specific responses. This is a classical signalling problem. Here, we draw parallels with the phosphorylation signalling pathway and we discuss the expanding repertoire of ubiquitin signals, signal tranducers and signalling-regulated E3 enzymes. We examine recent advances in the field, including a new mechanism of regulation of E3 ligases that relies on ubiquitination.